Elaboration of an Intermolecular Diels–Alder Adduct En Route to the Spiro-Fused Oroidin Alkaloids - Fulton, Brandon; Dias, Rasika; Gout, Delphine; Lovely, Carl J. (Synlett, 2025)
The dimeric oroidin alkaloids, exemplified by palau’amine, axinellamine, and massadine, remain challenging targets in the context of total synthesis owing to their compact and heteroatom-rich frameworks. A cycloaddition-rearrangement sequence has been developed using vinylimidazoles as substrates. The initial Diels–Alder adduct derived from urocanic acid and N-phenylmaleimide can be transformed into a lactone via a fluoride-induced ring-opening sequence. A twofold oxidation manifold affords the fully functionalized cyclopentane moiety present in palau’amine and congeners. Initial explorations to incorporate a second imidazole moiety are described.
Keywords: Cycloaddition; Oxidation; Alkaloid; Rearrangement; Ring opening